2005
DOI: 10.1111/j.1553-2712.2005.tb01963.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Complementary and Alternative Medicine Usage among ED Patients

Abstract: CAM usage was common among ED patients enrolled in our study, despite underreporting to ED staff. Given the growing evidence of benefits and hazards from popular CAM remedies and therapies, ED staff should consider raising this health issue with their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…Clinical settings such as hospitals are the interface between CAM users and conventional therapies. Previous studies of ED patients have identified a higher prevalence rate of CAM usage among ED patients compared to the general population [ 9 - 12 ]. This is because, the ED comprises of many categories of patients with chronic underlying diseases such as diabetes mellitus, cardiovascular system disorder, central nervous system disorder, asthma, and cancer that were associated with utilization of CAM therapy [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical settings such as hospitals are the interface between CAM users and conventional therapies. Previous studies of ED patients have identified a higher prevalence rate of CAM usage among ED patients compared to the general population [ 9 - 12 ]. This is because, the ED comprises of many categories of patients with chronic underlying diseases such as diabetes mellitus, cardiovascular system disorder, central nervous system disorder, asthma, and cancer that were associated with utilization of CAM therapy [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Read, Klomp, Mather, and Todd (2002) found that 46% of Americans reported using vitamin or mineral supplements. Since then, Carlson and Krahn (2006) found that 19% of persons with physical disabilities used CAM, and Kim et al (2005) found that 57% of emergency department patients reported CAM use in the past year. Wilson et al (2006) reported that 79% of adolescents had used CAM in their lifetime and 29.1% in the past month.…”
Section: Introductionmentioning
confidence: 99%
“…En las últimas décadas estamos viviendo un incremento de la popularidad de la medicina natural en los países desarrollados. En el marco de la medicina alternativa, el consumo de productos botánicos es el que mayor auge ha alcanzado y el que mayor incremento ha experimentado en las últimas décadas, estimándose una prevalencia actual entre un 18,6 y el 37% con amplias variaciones entre distintos países y tipos de estudios (1)(2)(3). Un estudio realizado en nuestro país señalaba que uno de cada cinco pacientes en tratamiento con medicamentos consumía hierbas medicinales de forma concomitante (4).…”
Section: Introductionunclassified